Digital signal processing a computer based approach - Mitra, Sanjit Kumar (McGraw-Hill series in electrical and computer engineering, 2006)
"Digital Signal Processing: A Computer-Based Approach" is intended for a two-semester course on digital signal processing for seniors or first-year graduate students. The author has taken great care to organize the chapters more logically by reordering the sections within chapters. More worked-out examples have also been included. The book contains more than 500 problems and 150 MATLAB exercises.